Holding, grasping and sensing of prosthetic robot arm like a real human hand, a journey beyond limits: An extensive review - Babu, Devin; Abdul, Nasir; A. S., Jamaludin; Muhammad Hisyam, Rosle (Springer, 2022)
This paper provides a comprehensive survey on the current state of prosthetic robotic arm; focusing on grasping strategy, sensing technologies, and control system. Numerous studies have been carried on prosthetic robotic arm field in improving its functionality. Mechanical/ prosthetic robotic arm is built to function as real—human-hand like for various fields like medical and industrial purposes. Starting from the design to details of every single compartment of the arm, up to providing the most needed function according to the purpose of the prosthetic robotic arm was built. The implementation method and system con-trol/architecture used are with proven experimental results that indicate each study's outcome is the primary concern. Although each developed prosthetic ro-botic arm differed between each other based on their purpose and technology used, aiming for the optimal design similar to human’s hand proves challenging for researchers, especially when it comes to the issue of practicality in whether it can be used to accomplish regular tasks a standard arm are able to.